RELASI ANTARA GENDING PONORAGAN DENGAN PROSES PAYAH DALAM PERTUNJUKAN JATHILAN DI KABUPATEN SLEMAN - Caecilia Maria Andriana Kristyanti; Muhammad Nur Salim; Nil Ikhwan (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
The research on the relationship between Gending Ponoragan and the process of payah performance in the Jathilan Krido Budoyo Turonggo Mudo in Sleman Regency reveals the form of Gending Ponoragan's presentation and its relationship with the process of payah formation. The word payah has various equivalent terms such as kerasukan, possession, or trance. This event became the highlight of the performance of Jathilan Krido Budoyo Turonggo Mudo. To reveal the relationship between Gending Ponoragan and the process of payah, Jankowsky's theory of music plays an essential role in stimulating trance experiences. It requires elements to be achieved in melody, rhythm, tempo and volume, and dynamics. In addition, Pilch's theory is also used to dissect issues related to the relationship between trance and music, which states that the best music that leads a person to experience a trance is music that has a regular number of beats and a repeating pattern based on a certain threshold or pitch level. However, the writer does not only look at the textual form of the music but also the context that surrounds it. The results of this study indicate that the activities of the association and the performance property support the process of payah and the conditions that must be met. The conditions for achieving payah include: spirit, offerings, handlers, sound system, dancers' behavior, situation or atmosphere of the performance, and musical presentation. The relationship between Gending Ponoragan and the process of payah does not occur directly but has a role in stimulating dancers to experience payah.